2021
DOI: 10.1096/fj.202101042r
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus‐encoded microRNA promotes viral replication by inhibiting type I interferon

Abstract: MicroRNAs (miRNAs), the non-coding RNAs of ~22 nucleotides (nt) in length, play a vital role in regulating viral replication. Hepatitis E virus (HEV), a singlestranded RNA virus, is a predominant pathogen of acute hepatitis worldwide.Virus-encoded miRNAs regulate the viral life cycle and escape from the host innate immune system. However, it is rarely known about HEV-encoded miRNA (HEV-miR-A6). In the present study, HEV-miR-A6 was screened by microarray, and further identified in vivo and in vitro. HEV-miR-A6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Li et al [41] reported that the anti-cancer drug gemcitabine inhibited HEV through inducing an interferon-like response via the activation of STAT1 phosphorylation. Human liver-derived organoids [42,43] and microRNA signatures in HEV infection [44,45] could be helpful for the development of antivirals against HEV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [41] reported that the anti-cancer drug gemcitabine inhibited HEV through inducing an interferon-like response via the activation of STAT1 phosphorylation. Human liver-derived organoids [42,43] and microRNA signatures in HEV infection [44,45] could be helpful for the development of antivirals against HEV infection.…”
Section: Discussionmentioning
confidence: 99%
“…HEV encodes a microRNA (miRNA), HEV-miRNA-A6, which can inhibit the phosphorylation of IRF3, thereby reducing the production of type I IFNs[ 53 ]. Moreover, HEV ORF-1 interferes with the recognition of viral RNA by RIG-I and impairs the activation of the JAK-STAT signaling pathway by inhibiting STAT-1 activation and nuclear translocation[ 54 , 55 ].…”
Section: The Main Elements and Characteristics Of The Immune Response...mentioning
confidence: 99%
“…Several viruses, including HEV, are known to encode miRNAs[ 53 ]. To illustrate, HEV-miR-A6 aids viral replication and deters the host’s innate immune response by inhibiting the expression of type I IFNs[ 53 ]. Additionally, the cellular miR-122 could boost HEV replication[ 144 ].…”
Section: Viral Factors Affecting Liver Failurementioning
confidence: 99%
“…The production of HEV-miR-A26 by HEV was confirmed in the cell transfection model, animal infection model and measurement of increasing miR-A26 levels in patient’s serum from an acute phase, vs. patients in convalescence phase of HEV infection. It is hypothesized that the main function of HEVmiR-A26 is to facilitate virus replication by suppressing the production of IFN-β [ 54 ].…”
Section: Hepatitis E Virus Mirnamentioning
confidence: 99%